Contribution of concrete to shear strength of rc beams failing in shear - Arslan, Guray; Polat, Zekeriya (Journal of Civil Engineering and Management, 2013)
Reinforced concrete (RC) beams with light transverse reinforcement are vulnerable to shear failure during seismic response. In order to prevent brittle shear failures at beam plastic hinge regions of earthquake-resistant structures, the Turkish Earthquake Code and ACI318 require the use of sufficient transverse reinforcement to resist the total expected shear demand. These codes tend to be excessively conservative and, in some cases, the contribution of the concrete to the shear strength is neglected. The aim of this study is to investigate the contribution of concrete to shear strength of RC beams failing in shear experimentally. The beams were tested under monotonically increasing reversed cyclic loading to determine the concrete contribution to shear strength. It is observed that the concrete contribution to the shear strength at ultimate state ranges from 18% to 69% of the ultimate strength.